A retrospective audit of pain assessment and management post caesarean section at New Somerset Hospital in Cape Town, South Africa - Munsaka, Effraim Frackson (Department of Anaesthesia and Perioperative Medicine, 2023)
Background: The most common major surgical procedure performed worldwide is the caesarean section (CS). Effective pain management is a priority for women undergoing this procedure, to reduce the incidence of persistent pain, (a risk factor for postpartum depression), as well as optimize maternal-neonatal bonding and the successful establishment of breastfeeding. Multimodal analgesia is the gold standard for post-caesarean section analgesia. At present, no perioperative pain management protocols could be identified for the management of patients presenting for CS at regional hospitals in South Africa. This audit aimed to review the folders of patients who underwent CS, with reference to perioperative pain management guidelines for CS. Methods: A descriptive, retrospective, cross-sectional audit was conducted. Three hundred folders (10% of the annual number of caesarean procedures performed) from New Somerset Hospital, a regional hospital in Cape Town, South Africa were reviewed. Results: The women were a mean age of 30 years (SD 6.2). Median gravidity was 3 (IQR 2-3) and parity was 1 (IQR 1-2); 52% had previously undergone a CS. In 93.3%, spinal anaesthesia was employed for CS. Pain assessment was poor, with only 55 (18%) patients having their pain assessed on the day of the operation. Analgesia was prescribed in over 98% of the patients, however, medication was only administered as prescribed in 32.6%. Non-steroidal anti inflammatory drugs (NSAIDs) were prescribed in < 1.67% of cases. None of the patients received a patient-controlled analgesia (PCA), transversus abdominis plane (TAP) block, or wound infusion catheter as supplementary strategies. Conclusions: Pain management for post-CS patient at this hospital is lacking. There is the need for the implementation of a structured assessment tool to improve administration of analgesics in these patients. In addition, the reasons for the omission of NSAIDs from the analgesia regimen requires investigation. Hospitals require post-CS pain protocols to guide management especially in resource-limited settings.